Energy and exergy of potato drying process via cyclone type dryer - Akpinar, EK; Midilli, A; Bicer, Y (Pergamon-Elsevier Science Ltd, 2005)
This paper is concerned with the energy and exergy analyses of the single layer drying process of potato slices via a cyclone type dryer. Using the first law of thermodynamics, an energy analysis was performed to estimate the ratios of energy utilization. An exergy analysis was accomplished to determine the location, type and magnitude of the exergy losses during the drying process by applying the second law of thermodynamics. It was concluded that the exergy losses took place mostly in the 1st tray where the available energy was less utilized during the single layer drying process of potato slices. It is emphasized that the potato slices are sufficiently dried in the ranges between 60 and 80 degrees C and 20-10% relative humidity at 1 and 1.5 ms(-1) of drying air velocity during 10-12 h despite the exergy losses of 0-1.796 kJ s(-1). (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: drying; energy analysis; exergy analysis; potato slices